An evaluation of the safety and operational benefits of traffic signal coordination for an urban arterials in Kuching - Kuo, Hie Hung (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study aims to investigate the effect of signal coordination on safety and operational benefits on an urban arterial in Kuching. Field data such as geometry, traffic volume and signal timing were collected at the study area during the peak hours in the morning and evening respectively and crash data for four years period were received in the form of police report from the Malaysia police department. The field data obtained were used as the inputs in the SIDRA software to determine the total vehicle travel time, average control delay per vehicle and total number of stops along the arterial road in Kuching which had been used as the measurement of effectiveness in evaluating the operational and safety benefits on an urban arterial. Subsequently, crash frequency prediction models were developed based on uncoordinated traffic signal systems during the morning and evening peak hours respectively in order to predict the frequency of the crash for coordinated traffic signal system by using SPSS software. By comparing the results obtained, the coordination of the traffic signal has significantly affect and improve the safety and operational performance along the urban arterial. The highest percentage of reduction in travel time is 12.9% during morning peak hour and 26.6% during evening peak hour. Meanwhile, the highest percentage of reduction in average delay is 16.6% during morning peak hour and 29.8% during evening peak hour. Besides, the average number of stops are reduced up to 23.3% during the morning peak hour and 28.4% during the evening peak hour. The highest percentage of reduction in average crash frequency is 96% during morning peak hour and 65.33% during evening peak hour after the coordination of traffic signal system.